Effect of irrigation and nitrogen application on water productivity and performance of Cotton (Gossypium sp.) - KUMAR, RAKESH; PAREEK, N. K.; RATHORE, V. S.; NANGIYA, VINAY (Journal of Soil and Water Conservation, 2019)
An experiment was conducted at research farm, Agricultural research sub-station, Hanumangarh, a unit of Swami Keshwanand Rajasthan Agricultural University, Bikaner during Kharif season, 2016 to study the effect of water and nitrogen application rates on yield attributes, yield and water productivity of cotton (Gossypium sp.). Cotton variety Sri ram 6588 BG II was planted using 3 levels of irrigation (200, 400 and 600 mm) and 4 level of nitrogen (0, 75, 150 and 225 kg ha-1) in split plot design with three replications. The water and nitrogen application rates had significant influence on yield attribute, yield and water productivity of cotton. The results indicated that the irrigation level 400 mm recorded significantly higher number of bolls per plant (37.08), boll weight (3.83 g), seed cotton yield (2568 kg ha-1), lint yield (734 kg ha-1) and seed yield (1834 kg ha-1) but was at par with irrigation level 600 mm. The highest stalk yield (4947 kg ha-1), biological yield (7599 kg ha-1) and seed index (9.21) were observed with irrigation level 600 mm. However, highest water productivity (0.405 kg m-3) was observed with irrigation level 200 mm. The maximum number of bolls per plant (41.78), stalk yield (4745 kg ha-1), biological yield (7462 kg ha-1) and water productivity (0.392 kg m-3) were found with nitrogen application rate 150 kg ha-1. The highest boll weight (4.05), seed index (8.47), seed cotton yield (2813 kg ha-1), seed yield (803 kg ha-1) and lint yield (2010 kg ha-1) were observed with nitrogen level 225 kg ha-1. The irrigation and nitrogen level had no significant effect on plant population at harvest. Irrigation along with nitrogen levels significantly influenced the yield attributes, yields and water productivity of Bt cotton. The combined application of irrigation level 600 mm and N @ 225 kg ha-1 resulted in significantly higher number of bolls per plant, seed cotton yield, stalk yield and total water productivity in comparison to irrigation @ 200 mm and N @ 0 kg ha-1 (control).